Correlation between Body Mass Index, Muscle Mass, and Muscle Explosive Power in First-Year Medical Students of Diponegoro University - Devi wahyu arum sari; Hafizhil Uzhma Al Ahmadi; Timothy Jordan; Buwono Puruhito; Edwin Basyar; Darmawati Ayu Indraswari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Abstract Background: Muscle explosive power as a component of physical fitness is an important factor that supports athletic performance in most sports. jump height and vertical jump performance in assessing explosive muscle power are influenced by various factors, including physiological, biomechanical, and anthropometric factors. Body mass index, muscle mass, and fat mass are important anthropometric factors in supporting jumping performance.Objective: To analyze the relationship between body mass index and muscle mass with legs muscle explosive power in first-year medical students of Diponegoro University.Methods: This study is an observational analytic study with a cross-sectional design. The subjects consist of 60 males and 108 females in first-year medical students of Diponegoro University who met the criteria. Body mass index and muscle mass were measured by Omron bioelectrical impedance analyzer, and muscle explosive power was measured by vertical jump test. Data were analyzed with the Kolmogorov Smirnov normality test and Spearman correlation test.Results: The average value of body mass index was 21.760±2.7734, muscle mass was 29.468±4.3283, and muscle explosive power was 29.468±4.3283. Muscle mass was positively correlated with legs muscle explosive power (p=0.00, R= 0.583) and negatively correlated between body mass index and legs muscle explosive power but it was not statistically significant (p=0.823 dan R=- 0.017) in first-year medical students of Diponegoro University.Conclusion: Muscle mass was positively correlated with legs muscle explosive power and body mass index showed no significant correlation with muscle explosive power. Keywords: body mass index, muscle explosive power, muscle mass, vertical jump test